Accident Risk Indices Of Malaysia’s Firefighters Working in 12 And 24 Hours Shift Works - Sharifah, Osman; Ismail, Bahari; Kadir, Arifin; Wan Mohd Nor, Hj. Ibrahim (Journal Occu. Safety & Health 9, 2012)
Work shift has been shown to correlate with accident rates. Understanding of such correlation is pertinent especially among emergency response personnel since the decisions that they make determines not only the outcome of their responses but also the risks of accidents to themselves. A questionnaire data derived study used together with a semi quantitative risk analysis method was adopted to estimate the levels of accident risks between firefighters working on two work shifts. Two hundred and forty eight Malaysia’s Fire and Rescue Department firemen from 24 fire stations working on shifts were selected as respondents. The accident rate among firefighters in year 2006 was 52.8 %. Results showed that the Accident Risk Index (ARI) among firefighters working the 24 hours shift was higher (ARI = 3.14) compared with those in the 12 hours shift (ARI = 2.98). However, there were no significant difference in overall severity of the accidents between the two shifts (p>0.05). The difference in risk levels was attributed to the difference in the likelihood of accident occurrence.